Arthroscopic Reduction and Fixation of Transverse Intra-articular Glenoid Fractures With Scapular Extension - Papadonikolakis, Anastasios (Arthrosc Tech, 2017)
The most common procedure to address transverse glenoid fractures that are characterized by intra-articular step-off or gapping is open reduction and internal fixation. Disadvantages of open surgery are delay in regaining full range of motion, increased approach morbidity, neurovascular complications, and the need for capsulotomy, which delays healing and increases the risk of stiffness. An arthroscopically assisted fracture fixation, as described in this article, is characterized by better visualization of the glenoid articular surface and reduction of the intra-articular fragments under direct vision, which diminishes the chances of residual step-off after fixation. Furthermore, arthroscopic fixation provides the advantages of minimal surgical trauma, which speeds up the recovery time, decreased morbidity as there is less blood loss compared with the open technique, lower chance of neurologic injury as there is less dissection around the spinoglenoid or suprascapular notch, less trauma to the joint capsule, and lower chances of stiffness and capsulorrhaphy arthropathy.